PENEGAKAN HUKUM TINDAK PIDANA PENYELUNDUPAN BARANG BEKAS OLEH KEPOLISIAN RESOR INDRAGIRI HILIR - Fardika, Devia Fitriana; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
IndonesiaThe problem of eradicating smuggling of used clothing will still be an interesting topic ofdiscussion among law enforcers, because this problem is one of the main objectives in carrying out lawenforcement duties and several negotiations related to licensing and licensing for the import and export ofgoods. State losses due to smuggling of used clothing reached trillions of rupiah. Law enforcement officialshave not been able to carry out effective enforcement and enforcement because both sanctions and sanctionsdo not provide a deterrent effect for the protectors. Law enforcers or the government have not been able tosave themselves for smuggling members because of the fact that there is still a lot of circulation of usedclothing. Adding to this proves that the pattern of law enforcement in the Tembilahan city area is still weakand does not run optimally, therefore, the author intends to examine the policies that have been implementedby the Tembilahan city government to connect increasingly illegal goods. The purpose of remembering thisthesis is: First to study the law enforcement of criminal acts of used goods recovery by the Tembilahan CityResort Police, Secondly to understand the contradiction in the law enforcement of criminal acts ofsmuggling of used goods by Tembilahan City Resort Police.This type of research is classified in sociological legal research. This legal research uses populationand sample research techniques, the data sources used are primary data, secondary data and tertiary data,while the data collection techniques in this study are by method of observation, interviews and libraryresearch.The results of the study can be concluded. First, Law Enforcement of criminal acts of smuggling ofused goods by Tembilahan City Resort police. Suggestions from research results The government should bemore assertive in combating the smuggling of used goods in Indonesia which is concentrated in the city ofTembilahan, and follow up on researchers who conduct rescue with assistance or assistance that can bedone by the deterrent.Keyword: Law Enforcement- Criminal Offense-Smuggling Of Used Goods-Tembilahan City Police.